Flashback mechanisms in lean premixed gas turbine combustion - Benim, Ali Cemal; Syed, Khawar Jamil (Academic Press, 2014)
Blending fuels with hydrogen offers the potential to reduce NOx and CO2 emissions in gas turbines, but doing so introduces potential new problems such as flashback. Flashback can lead to thermal overload and destruction of hardware in the turbine engine, with potentially expensive consequences. The little research on flashback that is available is fragmented. Flashback Mechanisms in Lean Premixed Gas Turbine Combustion by Ali Cemal Benim will address not only the overall issue of the flashback phenomenon, but also the issue of fragmented and incomplete research.